Development of a web application template for creating and managing databases of natural products from local biodiversity - Coelho, Ana Carolina Lunardello (2025)
In natural product research, dereplication-the process of identifying known compounds to avoid rediscovery-is essential. Recognizing this need, the Python library NPMINE (Natural Product MINing) was developed. This study focuses on the development of the NPMINE Online Database, which is derived from NPMINE, resulting in a web application based on the CRUD (Create, Read, Update, and Delete) model. This database is designed to efficiently store and explore manually collected data or information obtained from the scientific literature through the NPMINE library, including compounds and taxonomic names extracted from texts and images. It also allows users to include structures from other sources. The key features of the NPMINE Online Database include: (i) its open-source nature, encouraging collaboration and continuous improvement, (ii) free access and download options that cater to a broad user base, and (iii) customizable literature integration. In essence, the NPMINE Online Database has the potential to become a valuable open-access resource for chemical information on natural products.